GEOHERITAGE SITES IN THE TERRITORIAL UNIT “NORTH OF THE AUTONOMOUS PROVINCE OF KOSOVO AND METOHIJA” - Petrović, Dragan (Bulletin of Natural Sciences Research, 2026)
This paper presents an assessment of geoheritage sites in the territorial unit “North of the Autonomous Province of Kosovo and Metohija”, with the objective of identifying their scientific, educational, landscape–aesthetic, conservation, functional, and tourism values. The assessment of geoheritage sites was carried out using the Geosite Assessment Model (GAM), which enables an integrated, quantitative evaluation. The analysis encompassed five representative geoheritage sites and was based on data obtained from relevant scientific literature and field investigations. The results demonstrate that all analyzed sites exhibit medium to high values for the main indicators, confirming their considerable geoheritage potential. In contrast, the additional values are predominantly moderate, primarily due to insufficient protection measures, limited promotion, and underdeveloped tourism infrastructure. The identified imbalance between the main values and the level of their valorization underscores the need for a systematic and integrated approach to geoheritage management.